S. AND M. DYACHENKO’S NOVEL VITA NOSTRA AS A LANDMARK WORK IN THE HISTORY OF FANTASY LITERATURE - A. YU. Kuchinsky (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the novel Vita Nostra (2007) by S. and M. Dyachenko as a landmark work that transformed the creative trajectory of the renowned writing duo and significantly influenced the subsequent development of speculative fiction.